Dangerous Course and Atypical Termination of the Splenic Vein in Relation to Pancreas. A Case Report - Badagabettu, Satheesha Nayak; Shetty, Surekha D; Regunathan, Deepthinath; George, Bincy M; Mishra, Snigdha; Sirasanagandla, Srinivasa Rao (JOP. Journal of the Pancreas, 2014)
Context Knowledge of variations of the vessels closely related to the pancreas adds greatly to the success of pancreatic surgery. Splenic vein is one of the vessels that are closely related to the pancreas. Its variations might not only change the haemodynamics in the vein but also cause unexpected bleeding during pancreatic surgery. Case report During our dissection classes, we noted the variations in the course and termination of the splenic vein. After emerging from the spleen, it coursed upward and to the right, embedded in a groove on the anterior surface of body of pancreas. After reaching the upper border, it turned downwards and entered the body of the pancreas. After having a downward course in the body of pancreas, it emerged out and united with the superior mesenteric vein at an angle of about 160 degrees to form the portal vein. Conclusion This peculiar course of the vein might predispose it for thrombosis in case of pancreatitis. It can also lead to iatrogenic injuries during pancreatic or splenic surgeries. Image: Downward course of the splenic vein before joining the superior mesenteric vein.